Fiber consumption and dietary difficulties in childhood: contributing foods and associated factors - Nogueira, Luana Romão (2020)
Objectives: To describe fiber intake by children with feeding difficulties (FD) according to the recommendation of the Brazilian Society of Pediatrics (SBP), identify and describe the five foods that most contribute to fiber intake, and verify the factors associated with fiber consumption within the recommendation. Methods: This is a retrospective observational study, based on the use of data from medical records and with sampling assembled for convenience. The five foods that contributed most to fiber consumption (total, soluble and insoluble) were presented according to the percentage of contribution. The factors associated with fiber consumption within the recommendation were verified using logistic regression. Results: Most children (53.8%) had a consumption below the SBP recommendation. The major contributors to the total fiber intake were breads, rice and cereals, followed by fruits, beans and other pulses, vegetables and fruit juices. The contributors of soluble and insoluble fibers are similar to the total fiber rank. Parents’ education showed a positive association with fiber consumption within the recommendation (OR: 5.30; 95% CI 1.08-25.99; p = 0.039), while using distraction during the meal and lack of child autonomy to serve themselves showed a negative association (OR: 0.43; 95% CI 0.19-0.96; p = 0.040 and OR: 0.44; 95% CI 0.20-0.98; p = 0.045, respectively). Conclusion: Most children with FD presented fiber consumption below the recommendation. Most of contributing foods have good nutritional quality. The factors associated with fiber consumption were parents’ education, use of distraction during the meal and the child autonomy to serve themselves. Thus, the meals dynamics and the parentes role in food are important and should be evaluated and guided during the FD monitoring.